Association between polyunsaturated fatty acid intake and infertility among American women aged 20–44 years - Wang, Ruohan; Feng, Ying; Chen, Jiahe; Chen, Yingjiao; Ma, Fang (Frontiers in Public Health, 2022)
Background: Infertility is a nationwide public health priority in the U.S. However, few studies have investigated the effects of dietary intake of polyunsaturated fatty acids (PUFAs) on female infertility. This study explored the association between PUFA intake and risk of infertility. Methods: A total of 1785 women aged 20–44 years from three National Health and Nutrition Examination Survey cycles (2013–2018) were included in this cross-sectional study. The intake of PUFAs was obtained from a 24-hour dietary interview on two separate days with a 3–10-day interval, and nutrient residue models were used. Fertility status was assessed by positive response to two relative questions via a questionnaire. Logistic regression models were used and some covariates were adjusted. Results: Among all the participants, 340 (19.05%) women suffered from infertility. The intake of docosahexaenoic acid (DHA) (OR=0.998, 95% CI 0.998–0.999) was slightly related to the risk of infertility. When grouped into tertiles, compared with those in the lowest tertile, those in the upper tertile had a 27.1% (95% CI 0.553–0.960) lower risk. In contrast, women with higher octadecadienoic intake (OR=1.027, 95% CI 1.005–1.049) presented with a relatively higher risk of primary infertility. Furthermore, omega-6/omega-3 was not significant in women with either primary or secondary infertility. Conclusions: Our results suggest that PUFA intake is only slightly associated with infertility. The higher the DHA intake, the lower the risk of infertility regardless of age. In women with primary infertility, LA has negative effect.